SAT0527 Predictors of Disease Relapse in IgG4-Related Disease. (9th June 2015) - Wallace, Z.; Mattoo, H.; Mahajan, V.; Kulikova, M.; Lu, L.; Deshpande, V.; Choi, H.; Pillai, S.; Stone, J.
Abstract : Background: IgG4-related disease (IgG4-RD) is a relapsing-remitting condition responsible for fibroinflammatory lesions that can lead to organ damage and life-threatening complications at nearly any anatomic site (1). The duration of remission following treatment varies and predictors of relapse are unclear (2, 3). Objectives: To evaluate potential predictors of relapse in 60 patients treated with rituximab for active, biopsy-proven IgG4-RD. Methods: In this retrospective cohort study, all patients were treated with two doses of rituximab (1g) separated by 15 days. Clinical, radiographic, and laboratory data pertaining to rituximab response and disease relapse were collected from the electronic medical record. Kaplan-Meier curves were constructed to estimate the time to disease relapse. Log-rank analyses were performed to compare times to relapse among subgroups. Potential relapse predictors were evaluated with Cox regression analysis. Results: Of the 60 patients included, 57 (95%) had clinical responses to rituximab. Forty-one patients (68%) were treated without glucocorticoids. Twenty-one patients (37%) experienced relapses following treatment at a median time from the first infusion of 244 days (95% CI 158-330 days). Baseline concentrations of serum IgG4 and IgE and circulating eosinophil levels were predictors of disease relapses, with hazard ratios (HR) of 6.2 (95% CI 1.2-32.0), 8.2 (1.4-50.0), and 7.9 (1.8-34.7), respectively. Conclusions: Rituximab is an effective steroid-sparing agent but relapses following remission are common. Baseline elevations in serum IgG4 and IgE concentrations and blood eosinophil levels predict subsequent disease relapses. Measurement of these variables at baseline may assist in longitudinal management decisions for these patients. References: Stone JH, Zen Y, Deshpande V. IgG4-related disease. N Engl J Med 2012; Feb 9;366(6):539-51. Hart PA, Kamisawa T, Brugge WR, Chung JB, Culver EL, Czako L, et al. Long-term outcomes of autoimmune pancreatitis: a multicentre, international analysis. Gut 2013; Dec;62(12):1771-6. Yamamoto M, Nojima M, Takahashi H, Yokoyama Y, Ishigami K, Yajima H, et al. Identification of relapse predictors in IgG4-related disease using multivariate analysis of clinical data at the first visit and initial treatment. Rheumatology (Oxford) 2015; Jan;54(1):45-9. Disclosure of Interest: None declared